2000
DOI: 10.1247/csf.25.237
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Receptors for Glial Cell Line-derived Neurotrophic Factor (GDNF) and Neurturin in the Inner Blood-retinal Barrier of Rats.

Abstract: ABSTRACT. The retina is protected from somatic circulation by the blood-retinal barrrier (BRB) composed of tight junctions between retinal vascular endothelial cells (the inner BRB) and those between retinal pigment epithelial cells (the outer BRB). Our recent studies showed that glial cell line-derived neurotrophic factor (GDNF) secreted from astrocytes regulates the permeability of the BBB. In the present study, we immunohistochemically examined the expression of GDNF, neurturin (NTN) and their receptors, GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Our previous studies have demonstrated that GDNF is an important factor in regulating vascular permeability in vitro (12)(13)(14). Since it is possible that vascular permeability is determined by the balance between permeabilityinducing and -inhibiting factors, we therefore defined the antipermeability activity as the expression level of VEGF subtracted from that of GDNF in a given setting, where the cells treated with a vehicle were used as a control and defined as 100% in PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated that GDNF is an important factor in regulating vascular permeability in vitro (12)(13)(14). Since it is possible that vascular permeability is determined by the balance between permeabilityinducing and -inhibiting factors, we therefore defined the antipermeability activity as the expression level of VEGF subtracted from that of GDNF in a given setting, where the cells treated with a vehicle were used as a control and defined as 100% in PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While glial cell line-derived neurotrophic factor (GDNF) was originally identified as a neurotrophic differentiation factor for dopaminergic neurons in the central nervous system and retina (10,11), we have proposed the novel idea that GDNF secreted from glial cells is a critical factor in regulating the vascular permeability of the BRB in a biological unit comprised of capillary endothelial cells and glial cells via modulation of the barrier function of tight junctions (12)(13)(14). In addition, we have also demonstrated that certain advanced glycation end products that are formed under hyperglycemic conditions increase the vascular permeability of the BRB in vitro, which is achieved by the induction of VEGF and reduction of GDNF expression from glial cells, suggesting that phenotypic alteration of glial cells in diabetes is responsible for the BRB breakdown (12)(13)(14).…”
mentioning
confidence: 99%
“…They were stained overnight at 4°C with an affinity-purified rabbit polyclonal antibody raised against amino acids 350 to 363 mapping within the nuclear location signal (NLS) region of human NF-κB p50 [22] (Santa Cruz Biotechnology, Santa Cruz, Calif., USA; 2.0 µg/ml). For double-labelling immunofluorescence studies, they were then incubated with a goat polyclonal antibody against IL-8 (Santa Cruz Biotechnology; 1.0 µg/ml) or von Willebrand factor (vWF) (Santa Cruz Biotechnology; 1.0 µg/ml) [23,24,25]. NF-κB was visualized magnification as previously reported [26].…”
Section: Rna Extraction and Amplification By Rt-pcrmentioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor (GDNF), a growth factor in the TGF-β family is produced and secreted from astrocytes [59] and regulates the permeability of the BBB [60] and the BRB [17]. GDNF acts by a two-component receptor complex; 1) glycosylphospatidylinositol-linked cell surface molecule, the GDNF receptor GFRα-1, which acts as a ligand-binding domain, and 2) the receptor protein tyrosine kinase Ret, which acts as the signal transducing domain [61].…”
Section: Barrier Regulationmentioning
confidence: 99%
“…The necessity of glia and pericytes to induce the barrier has been demonstrated but it is just in its beginning [8]. The capillaries of the BRB seem to be similar to the capillaries of the BBB [14,17].…”
Section: Introductionmentioning
confidence: 99%